Mouse models of diffuse large B cell lymphoma - Tabatabai, Areya; Arora, Aastha; Höfmann, Svenja; Jauch, Maximilian; von Tresckow, Bastian; Hansen, Julia; Flümann, Ruth; Jachimowicz, Ron D.; Klein, Sebastian; Reinhardt, Hans Christian; Knittel, Gero (Frontiers in Immunology, 2023)
Diffuse large B cell lymphoma (DLBCL) is a genetically highly heterogeneous disease.Yet, to date, the vast majority of patients receive standardized frontline chemoimmune-therapy consisting of an anthracycline backbone. Using these regimens, approximately 65% of patients can be cured, whereas the remaining 35% of patients will face relapsed or refractory disease, which, even in the era of CAR-T cells, is difficult to treat. To systematically tackle this high medical need, it is important to design, generate and deploy suitable in vivo model systems that capture disease biology, heterogeneity and drug response. Recently published, large comprehensive genomic characterization studies, which defined molecular sub-groups of DLBCL, provide an ideal framework for the generation of autochthonous mouse models, as well as an ideal benchmark for cell line-derived or patient-derived mouse models of DLBCL. Here we discuss the current state of the art in the field of mouse modelling of human DLBCL, with a particular focus on disease biology and genetically defined molecular vulnerabilities, as well as potential targeting strategies.